2022
DOI: 10.1186/s12986-022-00684-2
|View full text |Cite|
|
Sign up to set email alerts
|

Protective and therapeutic effectiveness of taurine supplementation plus low calorie diet on metabolic parameters and endothelial markers in patients with diabetes mellitus: a randomized, clinical trial

Abstract: Background Taurine supplementation as a sulfur-containing amino acid may attenuate and/or alleviate diabetes-induced complications and endothelial dysfunction via its anti-inflammatory and antioxidant activities. Our purpose was to investigate the effect of Taurine supplementation on endothelial dysfunction markers, oxidative stress, inflammation, and glycemic control in patients with type 2 diabetes mellitus (T2DM). Methods In the current clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…In conclusion, we demonstrated that taurine plays a critical role in the manifestation of symptoms and incidence of adverse clinical outcomes in the PCC. Taurine supplementation has demonstrated diverse therapeutic properties, including anti-oxidation, anti-aging, antiepileptic, cytoprotective, and cardioprotective effects in many diseases, including diabetes, obesity, and dilated cardiomyopathy (DCM) [ 21 , 48 52 ]. Taurine is currently approved for heart failure treatment in Japan, and no toxicity has been reported in this context of clinical use [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we demonstrated that taurine plays a critical role in the manifestation of symptoms and incidence of adverse clinical outcomes in the PCC. Taurine supplementation has demonstrated diverse therapeutic properties, including anti-oxidation, anti-aging, antiepileptic, cytoprotective, and cardioprotective effects in many diseases, including diabetes, obesity, and dilated cardiomyopathy (DCM) [ 21 , 48 52 ]. Taurine is currently approved for heart failure treatment in Japan, and no toxicity has been reported in this context of clinical use [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recommended intake of nutrients, a well-balanced low-calorie-diet meal plan (3 main meals per day) was introduced to each psoriatic man. Meal-plan macronutrients contained the following items: fats (20–30%), proteins (10–15%), carbohydrates (55–65%), dietary fiber, as well as fruits/vegetables [ 15 ]. Men were interviewed every week to follow, discuss, and monitor their adherence to the suggested low-calorie-diet meal plan.…”
Section: Methodsmentioning
confidence: 99%
“…No results of clinical trials of Tau supplementation have been reported for DMD either; however, studies in metabolic disorders have generated encouraging results. In type 2 diabetes mellitus patients on a low-calorie diet, placebo-controlled administration of 1 g Tau three times per day for 8 weeks lead to a considerable decrease in serum insulin, along with improvement in inflammatory and oxidative stress markers [90]. In an open-label, phase III trial in mitochondrial myopathy, 9 to 12 g Tau per day for 52 weeks effectively reduced the recurrence of stroke-like episodes in patients suffering from lactic acidosis and stroke-like episodes (MELAS) [91].…”
Section: Adverse Effects and Human Clinical Trialsmentioning
confidence: 99%